Effect of Alkaloids Extracts From Solanum nigrum L.(Solanaceae) in DNA -Plasmid PBR322 by Using Gel Electrophoresis - Fayidh, M.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Four alkaloids compounds were extracted from the fruits and leaves, of plant known locally as (Anab AI-Thebe Solanum nigram), by various solvents systems, from an earlier study by the researcher. DNA tested its effect in plasmid PBR322 deportation method using Gel Electrophoresis. Results showed that two of those extract for full effectiveness digestible pieces of RNA and DNA plasmid, and digestive partly of the other alternatives. That could prove results indicate that this type of alkaloids consist of biological effectiveness of anti-twnors, through DNA digestion spare low molecular weight, as well as their effectiveness as antibacterial which had been found previously.